2006
DOI: 10.1158/1535-7163.mct-06-0447
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine synthetase as a causal, predictive biomarker for l-asparaginase activity in ovarian cancer cells

Abstract: L-Asparaginase (L-ASP), a bacterial enzyme used since the 1970s to treat acute lymphoblastic leukemia, selectively starves cells that cannot synthesize sufficient asparagine for their own needs. Molecular profiling of the NCI-60 cancer cell lines using five different microarray platforms showed strong negative correlations of asparagine synthetase (ASNS) expression and DNA copy number with sensitivity to L-ASP in the leukemia and ovarian cancer cell subsets. To assess whether the ovarian relationship is causal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 46 publications
3
71
0
2
Order By: Relevance
“…What is more, for NK/T cell lymphoma, we did not examine the genetic aberrations, and whether there is a potential relationship between gene fusion or other subtypes of aberrations and ASNS expression. Pancreatic and ovarian tumors and HCC with low ASNS expression levels have also been proposed for L-Asp therapy (17,20,29). In addition, one study revealed that this drug has an antiproliferative effect in β-catenin-mutated HepG2 cells (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, for NK/T cell lymphoma, we did not examine the genetic aberrations, and whether there is a potential relationship between gene fusion or other subtypes of aberrations and ASNS expression. Pancreatic and ovarian tumors and HCC with low ASNS expression levels have also been proposed for L-Asp therapy (17,20,29). In addition, one study revealed that this drug has an antiproliferative effect in β-catenin-mutated HepG2 cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the expression and the functional significance of ASNS have been investigated in solid tumors. ASNS was considered as a causal, predictive biomarker for L-Asp activity in ovarian cancer cells (16,17). Furthermore, one study also showed that the enhanced expression of ASNS protected pancreatic cancer cells from apoptosis induced by glucose deprivation and cisplatin (18).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty micrograms of total protein per lane was electrophoresed in sodium dodecyl sulfate (SDS)-polyacrylamide, transferred to Immun-Blot polyvinylidene difluoride membrane (Bio-Rad), and probed with antibodies against ASNS or b-actin (Sigma) as we reported previously. 25 Relative ASNS and b-actin expression levels were quantified using ImageJ. …”
mentioning
confidence: 99%
“…Lymphoid origin and solid tumors were prone to Lasparginase activity and showed resistant to the drugs among them soft tissue sarcoma [41], ovarian cancer [45], β-catenin mutated hepatocellular carcinoma [42], hepatocellular carcinoma with low expression of asparagine synthetase [43], and gastric adenocarcinoma [44] were studied. From the literature surveyed and reviewed L-asparaginase exhibited potent anti neoplastic and anti lymphomatic activity against tumors [1], [46], [29], [32], [40] This enzyme causes selective death of asparagines dependent tumor cells and also induces apoptosis in tumor cells [26].…”
Section: Assessment Of Anti-proliferative Activitymentioning
confidence: 99%